Louis IV of France at the Council of Ingelheim in 948 (engraving) - Auteur inconnu (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Louis IV of France at the Council of Ingelheim in 948 (engraving). Louis IV of France at the Council of Ingelheim in 948 (engraving)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons